The coming wave : technology, power, and the twenty-first century's greatest dilemma - Suleyman, Mustafa; Bhaskar, Michael (Crown, 2023)
"We are approaching a critical threshold in the history of our species. Everything is about to change. Soon you will live surrounded by AIs. They will organise your life, operate your business, and run core government services. You will live in a world of DNA printers and quantum computers, engineered pathogens and autonomous weapons, robot assistants and abundant energy. None of us are prepared. As co-founder of the pioneering AI company DeepMind, part of Google, Mustafa Suleyman has been at the centre of this revolution. The coming decade, he argues, will be defined by this wave of powerful, fast-proliferating new technologies. In The Coming Wave, Suleyman shows how these forces will create immense prosperity but also threaten the nation-state, the foundation of global order. As our fragile governments sleepwalk into disaster, we face an existential dilemma: unprecedented harms on one side, the threat of overbearing surveillance on the other. Can we forge a narrow path between catastrophe and dystopia? This groundbreaking book from the ultimate AI insider establishes 'the containment problem' -- the task of maintaining control over powerful technologies -- as the essential challenge of our age"--